Putative role of ischemic postconditioning in a rat model of limb ischemia and reperfusion: involvement of hypoxia-inducible factor-1α expression - Wang,T. (2014)
Hypoxia-inducible factor-1α (HIF-1α) is one of the most potent angiogenic growth factors. It improves angiogenesis and tissue perfusion in ischemic skeletal muscle. In the present study, we tested the hypothesis that ischemic postconditioning is effective for salvaging ischemic skeletal muscle resulting from limb ischemia-reperfusion injury, and that the mechanism involves expression of HIF-1α. Wistar rats were randomly divided into three groups (n=36 each): sham-operated (group S), hindlimb ischemia-reperfusion (group IR), and ischemic postconditioning (group IPO). Each group was divided into subgroups (n=6) according to reperfusion time: immediate (0 h, T0), 1 h (T1), 3 h (T3), 6 h (T6), 12 h (T12), and 24 h (T24). In the IPO group, three cycles of 30-s reperfusion and 30-s femoral aortic reocclusion were carried out before reperfusion. At all reperfusion times (T0-T24), serum creatine kinase (CK) and lactate dehydrogenase (LDH) activities, as well as interleukin (IL)-6, IL-10, and tumor necrosis factor-α (TNF-α) concentrations, were measured in rats after they were killed. Histological and immunohistochemical methods were used to assess the skeletal muscle damage and HIF-1α expression in skeletal muscle ischemia. In groups IR and IPO, serum LDH and CK activities and TNF-α, IL-6, and IL-10 concentrations were all significantly increased compared to group S, and HIF-1α expression was up-regulated (P<0.05 or P<0.01). In group IPO, serum LDH and CK activities and TNF-α and IL-6 concentrations were significantly decreased, IL-10 concentration was increased, HlF-1α expression was down-regulated (P<0.05 or P<0.01), and the pathological changes were reduced compared to group IR. The present study suggests that ischemic postconditioning can reduce skeletal muscle damage caused by limb ischemia-reperfusion and that its mechanisms may be related to the involvement of HlF-1α in the limb ischemia-reperfusion injury-triggered inflammatory response.